Fora de lugar : ação e reflexão na coordenação pedagógica em uma escola de sistema apostilado - Laurindo, Tânia Regina (2012)
This work recovers the author s effective practice as the pedagogical coordinator in a school where booklets are used in its teaching system. The coordination happened during the school year of 2010 and the first semestre in 2011. There was not, initially, any pretension of transforming the effective professional activity into an object of analysis and reflection. As a result, the recovery of developed actions was made later through narrative, recovery of documents and interviews with the teachers involved in the process. Transforming one s own experience into an object of study has placed forward two methodological issues: the action research and the narrative investigation. There are things put into action, there is rememoration of action. This work crosses paths with the methodological investigation of both perspectives. The professional work had two great thinkers as references: Freinet and Bakhtin. The invariables and the Freinetian pedagogical instruments were recalled in the exposition due to their key role in the professional activity which was developed and analysed; the dialogic principles and the principles of the relationship with the alterity as a constituent form of the subjectivities have oriented the relationships with the teachers who participated in the research. For that reason they were recalled as a theoretical basis for the work. The look based on those two authors allowed the researcher to find the existing gaps in a school where bookets were used for pedagogical actions distinct from those expected by the system. Other possibilities of work in the classroom and at school were gradually built during the mentioned period by the author, who chose to do so instead of exercising the role of coordinator within the predicted limits of activity control. The actions with two teachers from the second year of the fundamental level (with children in the process of alphabetization) are related and analysed showing a recalling process by the teachers in their pedagogical practice. This, however, crucially depends on concrete support in other possibilities of action, which leads to the conclusion that the teacher only faces the challenge when he feels his feet are on solid ground, a motto of Freinet s pedagogy. Building an environment of transition with feet on solid ground was the task of the pedagogical coordination which demanded from the professional the exercise of a job pedagogically supported by a conception of education in order to supply students and teachers with bases for their highest , though somehow uncertain, expectations.